Electronic Reducibility Scales with Intergranular Interface Area in Consolidated In2O3 Nanoparticles Powders - Thomele, Daniel; Siedl, Nicolas; Bernardi, Johannes; Diwald, Oliver (Journal of Physical Chemistry C, 2016)
Interfaces between nanoparticles of reducible metal oxides play a critical role for stoichiometry changes and associated self-doping effects. We explored the susceptibility of consolidated In2O3 nanoparticle ensembles exhibiting enhanced concentrations of intergranular interfaces toward vacuum annealing induced lattice oxygen depletion. Dielectric loss effects observed for nonstoichiometric In2O3–x nanoparticles inside the cavity of an Electron Paramagnetic Resonance (EPR) spectrometer system were used to determine trends in oxygen deficiency and n-type doping level for differently consolidated nanoparticle powders. Moreover, interfacial electron transfer from the In2O3–x nanoparticles to O2 was utilized to evaluate the abundance of paramagnetic O2δ− adsorbates as a function of different levels of nanoparticle consolidation. Both particle aggregation inside aqueous nanoparticle dispersions, which is driven by capillary forces, and mechanical powder compaction were employed for the adjustment of intergranular interface area. For the first time, we observed a clear correlation between reducibility of In2O3–x nanoparticles achieved by vacuum annealing and the amount of intergranular interface area. This study clearly underlines the multiple role of intergranular interfaces. Inside ensembles of semiconducting oxide nanoparticles, they not only provide diffusion paths for charge carriers, but also offer a handle to adjust the n-type doping level via heat treatment in vacuum or other reducing gas atmosphere